Modeling and simulation of metal organic halide vapor phase epitaxy growth chamber reactor / Nurul Zieyana Mohamed Annuar - Nurul Zieyana , Mohamed Annuar (2013)
Over the last few decades, there was a substantial appeal on the growth of galliumnitride (Ga-N) based alloy for high performance optoelectronic devices such as blue/violet laser diode (LD), blue/white light emitting diode (LED) etc. In the recent years, there have been revolutionary changes in semiconductor field. Growth method for GaN-based film has been extensively explored, with success of thick film growth using halide vapor-phase epitaxy (HVPE) technique The theoretical changes were attributed from the experimental results where modeling was vastly used for the purpose of design of equipment. This is because of the cost of the equipment and it is one of the major burdens in semiconductor processing. In conjunction with reactor design, several studies have focused on the simulation for optimizing the flow pattern to produce uniformity in the system. To address these issues, a new development called metal organic halide vapor phase epitaxy (MOHVPE) reactor has been proposed in this study. The model is conjugated with comprehensive detailed simulation for horizontal tube reaction chamber by using computerized software. The development consists of 5 inlet nozzles with dimension of 54 cm long. The numerical study of horizontal MOHVPE growth shows dependence on temperature and species flow rates. The inlet area is set to room temperature while the whole chamber is set in the temperature range from 1273 K to 1473 K. Improvements of growth process reactor geometry aim that the velocity gas efficiency, temperature distribution stabilization and uniformity control flow pattern between the substrate holders are discussed. It is seen that the flow pattern is influenced by the temperature distribution and geometry of the chamber. The numerical study of horizontal MOHVPE growth shows a function of temperature and species flow rates has been performed with specific condition to find the ideal position of the substrate for growth process in future.